PROGRAMA SAÚDE NA ESCOLA: IDENTIFICAÇÃO DAS AÇÕES DE PROMOÇÃO DA ALIMENTAÇÃO SAUDÁVEL, PERFIL DO CONSUMO ALIMENTAR E ESTADO NUTRICIONAL DE ESCOLARES NO ESTADO DO MATO GROSSO DO SUL - Lorena Laira Morais dos Santos (2023)
Introduction: Health and education constitute a field of intersectoral policy of significant relevance to the quality of human and social life. Talking about health, referring to what is done at school and what is done at the Basic Health Unit (UBS) requires a comprehensive look, which can achieve the necessary intersection for the development of actions that contemplate the intentions of both areas and that have the reality of the students as their context. and its possibilities of giving new meaning to knowledge and practices in favor of improving living conditions. In this context, the School Health Program (PSE) is inserted, which aims at the integration and permanent articulation of education and health, providing an improvement in the quality of life of the Brazilian population. Objective: to verify the development of actions to promote healthy eating and prevent childhood obesity in the PSE, as well as the nutritional profile and food consumption of schoolchildren in the period from 2019 to 2021 in the state of Mato Grosso do Sul. Methodology: this is of an ecological and retrospective, cross-sectional study, with documentary analysis and a quantitative approach with data obtained through the databases of the Ministry of Health e-SUS, available in the information systems: Department of Family Health (DESF), Sistema of Food and Nutritional Surveillance (SISVAN), Health Information System for Primary Care (SISAB) and e-Gestor Platform. Result: Regarding the number of PSE actions carried out focusing on healthy eating and the number of participants, it was possible to observe a drop, these differences between 2020 and 2021 can be attributed to the implications of the COVID-19 pandemic in Brazil, which, among many other effects and impacts, converged to the closure of schools. Regarding the food consumption profile, there was an increase in all categories (sex and age) in the percentage of consumption of sugary drinks, sweets and ultra-processed foods in 2021 compared to 2019. In relation to the nutritional profile there were also differences between the sexes analyzed, with that males were more likely to be at risk of overweight and obesity when compared to females. Conclusion: Given the change in the nutritional and dietary profile of schoolchildren and society as a whole, it appears that childhood obesity is an important public health problem, and its prevention is among the actions to be developed by the PSE. It is possible to develop intersectoral educational actions to promote healthy eating in basic services involving schoolchildren and their families. These actions must be prioritized on public agendas in order to enable their daily practice in services as well as recognizing the importance of the School Health Program, as a strategy for health promotion and disease prevention. Descriptors: Primary Health Care; Health Promotion Assessment; Child obesity; School Health Services; Nutritional Surveillance